HEPATOPROTECTIVE EFFECT OF 50% ETHANOL EXTRACT OF SEAGRASS RHIZOME (CYMODOCEA ROTUNDATA) AGAINST LIVER TISSUES IN PARACETAMOL-INDUCED RATS - Dewi, Renita; Malika, Raesha Dwina; Meilani, Ade Mara; Saputri, Fadlina Chany (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to determine the hepatoprotective effect of 50% ethanol extract of seagrass rhizome in terms of serum glutamic oxaloacetic transaminase (SGOT) and serum glutamic pyruvic transaminase (SGPT) activities in paracetamol-induced rat plasma. Methods: This study included 28 male, white rats randomly divided into seven groups. Groups I and II represented the normal control and control groups, respectively, administered with 280 mg/kg BW of rhizome extract. Group III represented the negative control group induced by a suspension of paracetamol (2g/kg BW). Group IV represented a positive control group administered with Hepa-QÂ® at a dosage of 150 mg/kg BW. Groups V, VI, and VII were administered with seagrass rhizome extract at doses of 140, 280, and 560 mg/kg BW, respectively, before paracetamol induction. The test material was orally administered for 17 days. On days 12â€“17, the rats were induced with paracetamol through the same route. On day 18, blood sampling was performed followed by SGOT and SGPT plasma measurements. Results: Our results revealed that seagrass rhizome extracts could significantly decrease SGPT and SGOT levels in paracetamol-induced rats (p<0.05) compared with those in the negative control group. Conclusion: Thus, seagrass rhizome extracts possess the potential for development as a hepatoprotective agent.